Convergence in reduced body size, head size, and blood glucose in three island reptiles. Issue 12 (20th May 2018) - Sparkman, Amanda M.; Clark, Amanda D.; Brummett, Lilly J.; Chism, Kenneth R.; Combrink, Lucia L.; Kabey, Nicole M.; Schwartz, Tonia S.
Abstract: Many oceanic islands harbor diverse species that differ markedly from their mainland relatives with respect to morphology, behavior, and physiology. A particularly common morphological change exhibited by a wide range of species on islands worldwide involves either a reduction in body size, termed island dwarfism, or an increase in body size, termed island gigantism. While numerous instances of dwarfism and gigantism have been well documented, documentation of other morphological changes on islands remains limited. Furthermore, we lack a basic understanding of the physiological mechanisms that underlie these changes, and whether they are convergent. A major hypothesis for the repeated evolution of dwarfism posits selection for smaller, more efficient body sizes in the context of low resource availability. Under this hypothesis, we would expect the physiological mechanisms known to be downregulated in model organisms exhibiting small body sizes due to dietary restriction or artificial selection would also be downregulated in wild species exhibiting dwarfism on islands. We measured body size, relative head size, and circulating blood glucose in three species of reptiles—two snakes and one lizard—in the California Channel Islands relative to mainland populations. Collating data from 6 years of study, we found that relative to mainland population the island populations had smaller body size (i.e., island dwarfism), smaller head sizes relative to body size, and lower levels of blood glucose, although with some variation by sex and year. These findings suggest that the island populations of these three species have independently evolved convergent physiological changes (lower glucose set point) corresponding to convergent changes in morphology that are consistent with a scenario of reduced resource availability and/or changes in prey size on the islands. This provides a powerful system to further investigate ecological, physiological, and genetic variables to elucidate the mechanisms underlying convergent changes in life history on islands. Abstract : We tested for evidence of convergent changes in body size, relative head size, and blood glucose in three species of reptiles living in the California Channel Islands. We found that on the islands all three species had smaller body sizes and relative head sizes, and consistently low blood glucose that was generally lower than their mainland counterparts. These findings support a role for resource limitation generating convergent changes in both morphology and physiology on islands, and deepen our understanding of the widespread phenomenon of dwarfism on islands worldwide.